1993
DOI: 10.1530/acta.0.1290322
|View full text |Cite
|
Sign up to set email alerts
|

Pentoxifylline inhibits the proliferation and glycosaminoglycan synthesis of cultured fibroblasts derived from patients with Graves' ophthalmopathy and pretibial myxoedema

Abstract: Excessive amounts of glycosaminoglycans accumulate in the extraocular muscles of patients with Graves' ophthalmopathy and in the affected skin of patients with pretibial myxoedema. It is widely accepted that fibroblasts are the sources of glycosaminoglycan synthesis. Pentoxifylline, an analogue of the methylxanthine theobromine, inhibits the proliferation and certain biosynthetic activities of fibroblasts derived from normal human skin and from skin of patients with some fibrotic disorders. Our objective was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(39 citation statements)
references
References 0 publications
0
38
0
1
Order By: Relevance
“…It has also been reported that pentoxyfylline (Berman & Duncan, 1989;Aulthouse et al ., 1992;Chang et al ., 1993) and methylprednisolone (Laato et al ., 1989) have inhibitory effects on the synthesis of proteoglycans, glycosaminoglycans, collagen IV and fibronectin determined in amyloid (Skogen et al ., 1980;Lyon et al ., 1991;Gallo et al ., 1994;Ancsin & Kisilevsky, 1997;Landman et al ., 1998b).The role of pentoxyfylline and methylprednisolone in the prevention of amyloidosis should further be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been reported that pentoxyfylline (Berman & Duncan, 1989;Aulthouse et al ., 1992;Chang et al ., 1993) and methylprednisolone (Laato et al ., 1989) have inhibitory effects on the synthesis of proteoglycans, glycosaminoglycans, collagen IV and fibronectin determined in amyloid (Skogen et al ., 1980;Lyon et al ., 1991;Gallo et al ., 1994;Ancsin & Kisilevsky, 1997;Landman et al ., 1998b).The role of pentoxyfylline and methylprednisolone in the prevention of amyloidosis should further be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…A rise in intracellular cAMP has been suggested as a pentoxyfylline-mediated inhibitory effect on the respiratory burst of neutrophils (Besler et al ., 1986). Furthermore, pentoxyfylline has been shown to inhibit the synthesis of glycosaminoglycan, the production of fibronectin in cultured fibroblasts, the activity of collagenase and TNF-a (Berman & Duncan, 1989;Chang et al ., 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Concerning this latter effect, the bulk of the available experimental evidence is so far limited to sound studies performed on dermal fibroblasts (Berman et al, 1989;Chang et al, 1993;Duncan et al, 1995), in which, however, very little attention has been paid to an important aspect of fibrogenesis, namely Effect of PTF on intracellular cyclic AMP levels in human HSCs…”
Section: Discussionmentioning
confidence: 99%
“…In vitro studies, performed in cultured dermal fibroblasts, have suggested that PTF may exert an antifibrogenic effect by reducing the synthesis of extracellular matrix (ECM) components, including collagen type I and type III, by increasing collagenase activity, and by decreasing cell proliferation (Berman et al, 1989;Chang et al, 1993;Duncan et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…This drug, an analogue of methylxanthine theobromine widely used for peripheral vascular disorders, has complex immunomodulatory effects on cytokine production 79 . Pentoxifylline inhibits proliferation and glycosaminoglycan synthesis of cultured orbital fibroblasts derived from GO patients 80 . In addition, this drug blocks glycosaminoglycan production and HLA-DR expression induced by IL-1, TNF-á and IFN-ã in orbital fibroblasts 81 .…”
Section: Cytokine Antagonistsmentioning
confidence: 99%